STUDIES ON WATER QUALITY AND FISH ABUNDANCE IN BALANGA RESERVOIR, GOMBE STATE, NIGERIA - admin, ABUBAKAR, B; KABIRU, M.,; SUNDAY , NABOTH; ZAINAB, I. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Water quality and fish abundance in Balanga dam, Gombe state, Nigeria was studied over a period of three months (October, November and December). The water quality of balanga reservoir was optimum between the sites and months from October to December which is within the survival value of fish species when compared the world health organization (WHO 2021). The result of the physico - chemical parameters showed that the temperature of the reservoir, pH ,The electrical conductivity, The total dissolved solids, the turbidity , the dissolve oxygen and the total hardness shows no significant differences between the months and sites ( P > 0.05). A total of ten (10) fish species were identified from Balanga Dam for the period of three months from October to December 2022. These fish species represent a total of seven (7) families. Relative abundance of fish species identified in Balanga Dam indicate that, oreochromis niloticus had the highest relative abundance with the total number of 638 individual species of fish.The fish Species oreochromis niloticus, oreochromis aureus and Brycinus nurse had the highest percentage with the percentage of 43.37%, 40.24% and 11.83% respectively. Followed by bagrus bayad with 2.11%, while clarias gariepinus, labeo senegalensis , lates niloticus, mormyrus macrophthalmus, mormyrus rume, and Auchenoglanis occidentalis had 0.68%, 0.54%, 0.41%, 0.41%, 0.20% and 0.20% respectively of the total fish catches.